Virtualisasi Toleransi Beragama: Rekognisi Netizen Lintas Agama Atas Patung Yesus Burake di Tanah Toraja Sulawesi Selatan - Popang, Kiki Clara; Lattu, Izak Y.M.; Tampake, Tony; Supratikno, Agus (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
This study aims to examine the shift in religious tolerance from factual space to virtual space through the Jesus Burake statue. The research subjects are Toraja people and Netizens in virtual space. The research method that will be used is qualitative with the type of digital ethnography research. The author raises the Burake Jesus Statue as one of the religious tourism objects in Toraja that has become a shared space. This phenomenon will be studied using Axel Honneth's theory of Recognising the principles of love, law and solidarity. Izak Lattu's ‘Click Ritual’ theory to analyse how netizen click rituals on social media bring narratives of peace in virtual spaces. The author finds that the statue of Jesus Burake has become a shared space for interfaith people in South Sulawesi. Several interfaith activities were conducted at the statue, such as a joint prayer for world peace, raising the red and white flag during the Indonesian Independence Day and planting 1,000 trees. Documentation of these activities shared on social media gave rise to narratives of tolerance and peace. So that virtual space becomes a creative new space to strengthen attitudes of tolerance between religious communities.